ANALISIS FIKIH TERHADAP AKAD DANA TALANGAN HAJI PADA BANK SYARIAH - Novindri, Silvi (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2013)
Financing bailout of Hajj is loans from Islamic banks to customers to cover theshortage of funds in order to gain seats (seat) at settlement BPIH Hajj (Pilgrimage Travel Expenses). This financing product uses the principle of Qardh Wal Ijarah. The purpose of this study was to determine the views of Islamic law to finance bailouts of pilgrimage and to know the views of Islamic law about the fee ujrah on contract bailouts of pilgrimage. This research is a field research. The design of this study used a qualitative approach to the non-statistical analysis. While the data analysis techniques used content analysis and interactive method which consists of data reduction, data collection, data presentation and conclusion. The results of this research note that the view of Islamic law against the bailouts of pilgrimage on Islamic bank containing multi-contract, where the contract is used qardh and Ijarah are allowed. While the view of Islamic law regarding fee ujrah decision on the bailout fund of pilgrimage is not appropriate with shariah because of the percentage of fee ujrah based on funds qardh